Governance and sustainability - Crowther, David; Seifi, Shahla (Developments in corporate governance and responsibility ;, 2020)
Both firms and governments are increasingly taking steps to address sustainability, and at the same time the issue of governance has become more prominent due to the numerous problems in public and business life which have manifest failures in governance. As initiatives for sustainability increase in importance and prominence, so has the need for governance of sustainability plans and actions. This volume of Developments in Corporate Governance and Responsibility responds to that need and focuses on the relations between governance and sustainability. The book looks at what has been happening in various locations around the world, identifying varying approaches and examining whether and how a best practice could be developed. Gathering contributions that are varied in scope and produced by authors from around the world, it provides a rich picture of the progress (or lack of progress) being made in a wide array of contexts. For its depth and broad scope, Governance and Sustainability is a must-read for researchers, students, and practitioners interested in sustainability and corporate social responsibility.